An MEKC assay for the therapeutic drug monitoring of cefepime. Issue 17 (15th July 2013) - Theurillat, Regula; Sendi, Parham; Thormann, Wolfgang; Svec, Frantisek
<x xml:space="preserve">Abstract</x> The development of a robust assay based on MEKC for cefepime in human serum and plasma with internal quality assurance is reported. Sample preparation comprises protein precipitation in the presence of SDS at pH 4.5. This is a gentle approach for which decomposition of cefepime during sample handling is negligible. After hydrodynamic sample injection of the supernatant, analysis occurs in a phosphate/borate buffer at pH 9.1 with 75 mM SDS using normal polarity and analyte detection at 257 nm. The MEKC run time interval and throughput are about 5 min and seven samples per hour, respectively. The calibration range for cefepime is 1–60 μg/mL, with 1 μg/mL being the LOQ. The performance of the assay with multilevel internal calibration was assessed with calibration and control samples. The assay is shown to be simple, inexpensive, reproducible, and robust. It was applied to determine cefepime levels in the sera of critically ill patients and to assess the instability of cefepime in patient and control samples. Our data revealed that serum containing cefepime can be stored at ‒20°C for a short time, whereas for long‐term storage, samples have to be kept at ‒70°C.